2018
DOI: 10.21608/jppp.2018.41677
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of some Different Insecticides against Cotton Mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) and its Associated Predators

Abstract: The cotton mealybug, Phenacoccus solenopsis Tinsley is an invasive polyphagous pest species causing severe economic damage to a wide range agricultural crops. Five different toxicants of different groups were evaluated for their effectiveness in reducing mealybug incidence on cotton under both laboratory and field conditions as well as their effectiveness against its associated predators (Chrysoperla carnea (Steph.), Hyperaspis vinciguerrae Capra) under field conditions. Chlorpyrifos and Imidacloprid were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
2
12
0
Order By: Relevance
“…Beauveria bassiana was found to be least effective against this pest. These results were in conformity with El-Mageed et al [16] who reported that Imidacloprid reduced Phenacoccus solenopsis population up to 77.82 per cent on cotton.…”
Section: Efficacy Of Insecticides Against Mealy Bugs Phenacoccus Sole...supporting
confidence: 92%
“…Beauveria bassiana was found to be least effective against this pest. These results were in conformity with El-Mageed et al [16] who reported that Imidacloprid reduced Phenacoccus solenopsis population up to 77.82 per cent on cotton.…”
Section: Efficacy Of Insecticides Against Mealy Bugs Phenacoccus Sole...supporting
confidence: 92%
“…The IGRs control of pests species is far higher than traditional insecticides and are substantial alternative for integrated pest management (IPM) program in targeted insect pest control [30]. The cotton mealybug is an invasive species of polyphagous insects that cause severe economic damage to many crops particularly cotton [31].…”
Section: Discussionmentioning
confidence: 99%
“…Abd El-Mageed et al, (2018) concluded that chlorpyrifos was significantly the most effective in reducing the cotton mealybug population followed by imidacloprid, emamectin benzoate and buprofezin with average reduction between (96, 24 and 43.99%). Our results were in agreement with the result obtained by El-Zahi et al, (2016) where they studied the efficacy of eight toxic products belonging to different chemical groups against mealybug P. solenopsis on cotton under field conditions and found that methomyl imidacloprid, thiamethoxam and chlorpyrifos had the highest efficacy against P. solenopsis recording 92.3 to 80.4 reduction of the insect population.…”
Section: Efficacy On Mealybugmentioning
confidence: 99%